Peningkatan Kapasitas dan Manajemen Keuangan Industri Kerupuk Balok melalui Program Kemitraan Masyarakat di Desa Bukit Peninjauan II Kecamatan Sukaraja Kabupaten Seluma, Bengkulu - Hesti Nuraini; Evi Andriani; Dewi Suranti (Universitas Mathla'ul Anwar Banten, 2019)
CAPACITY BUILDING AND FINANCIAL MANAGEMENT OF THE KERUPUK BALOK INDUSTRY THROUGH A COMMUNITY PARTNERSHIP PROGRAM IN BUKIT PENINJAUAN II VILLAGE, SUKARAJA DISTRICT, SELUMA DISTRICT, BENGKULU. Bukit Peninjau II Village, Sukaraja Subdistrict, Seluma Regency, has very good potential for the development of small industries, especially home industries in the food sector. One of the small industries in Bukit Peninjauan II Village is the block cracker processing industry which was started in 1995 and currently has 8 business units, including the Usaha Maju and the Raos Echo Community. The team together with partners agreed on several issues faced by partners, including the lack of knowledge (soft skills) and skills mastered by partners regarding product diversification technology, packaging techniques, production equipment and knowledge about financial management. The aim of the Community Partnership Program is to improve partners' skills in the field of product diversification, improvement of packaging and labeling techniques, application of drying system mechanization technology, and increasing partner knowledge in the field of financial management of small industries. The results of the activity show that the product of processed cracker diversification has been formed in the Usaha Maju and the Raos Echo Community, with 3 variants namely original, spinach and carrots crackers. Furthermore, improvements have also been made to the quality of packaging and labeling, through training and providing assistance with labeling equipment. To overcome the problem of drying which has so far been using sunlight, the team provided cabinet drying assistance to the two partners.